Bad things [videorecording (DVD)] - Rankin, Gayle; Nef, Hari, 1992-; Dexter-Jones, Annabelle; Ringwald, Molly (Shudder, 2023)
When a group of friends escapes the city to spend the weekend in an abandoned hotel, a pervading eerie energy begins to illuminate the cracks in their little family unit.